Do Iron Oxide Nanoparticles Have Significant Antibacterial Properties? - Sergey V. Gudkov; Dmitriy E. Burmistrov; Dmitriy A. Serov; Maksim B. Rebezov; Anastasia A. Semenova; Andrey B. Lisitsyn (MDPI AG, 2021)
The use of metal oxide nanoparticles is one of the promising ways for overcoming antibiotic resistance in bacteria. Iron oxide nanoparticles (IONPs) have found wide applications in different fields of biomedicine. Several studies have suggested using the antimicrobial potential of IONPs. Iron is one of the key microelements and plays an important role in the function of living systems of different hierarchies. Iron abundance and its physiological functions bring into question the ability of iron compounds at the same concentrations, on the one hand, to inhibit the microbial growth and, on the other hand, to positively affect mammalian cells. At present, multiple studies have been published that show the antimicrobial effect of IONPs against Gram-negative and Gram-positive bacteria and fungi. Several studies have established that IONPs have a low toxicity to eukaryotic cells. It gives hope that IONPs can be considered potential antimicrobial agents of the new generation that combine antimicrobial action and high biocompatibility with the human body. This review is intended to inform readers about the available data on the antimicrobial properties of IONPs, a range of susceptible bacteria, mechanisms of the antibacterial action, dependence of the antibacterial action of IONPs on the method for synthesis, and the biocompatibility of IONPs with eukaryotic cells and tissues.